What do Residents Consider to be Gambling and What are Their Attitudes Towards it? Evidence from the Czech Republic - Fiedor, David; Král, Ondřej; Frajer, Jindřich; Šerý, Miloslav; Szczyrba, Zdeněk (Journal of gambling studies, 2019)
The aim of the article is to contribute to an understanding of the attitudes of post-communist Europe's inhabitants towards gambling, and of their opinions concerning which activities can be regarded as gambling. The Attitudes Towards Gambling Scale (ATGS-8) questionnaire was used in the survey, ensuring the international comparability of the results. For the subsequent in-depth analysis of attitudes we mainly used multidimensional statistical methods. The survey, conducted in 2017, had 1092 respondents. The least negative attitudes to gambling were found in the younger age groups, while the attitudes of senior citizens were the most negative. Concerning participation in gambling, 68.4% of the respondents had taken part in at least one of the range of gambling activities offered as choices. Participation in gambling is an important factor influencing the overall attitude of the respondents to gambling. Of equal importance was the range of intensity in their perceptions of which games can be considered to be gambling, with four similarly perceived types of gambling identified. The research shows that gambling is perceived negatively by the population of the Czech Republic. The explanation may be found in the substantial media coverage of gambling related to changes in the legislation and the tightening of restrictions.
Keywords: Socioeconomic Factors; Young Adult; Central and Eastern Europe; Male; Subtypes; mladý dospělý; Attitude to Health; Attitude; Česká republika; veřejné mínění; socioekonomické faktory; hráčství; Life Style; mužské pohlaví; Questionnaire; průzkumy a dotazníky; Public Opinion; návykové chování; Czech Republic; životní styl; lidé; ženské pohlaví; Humans; Gambling; postoj ke zdraví; Behavior, Addictive; Female; Surveys and Questionnaires